MILK YIELD, MILK COMPOSITION AND BLOOD METABOLITE PROFILES IN DAIRY COWS SUPPLEMENTED WITH VITAMIN D ENRICHED YEAST - Hnokaew, Patipan; Seepai, Apichart; Moonmanee, Tossapol; Phatsara, Chirawath; Chongkasikit, Nattaphon; Yammuan-Art, Saowaluck (LIFE: International Journal of Health and Life-Sciences, 2024)
The purpose of this study was to evaluate the effect of vitamin D enriched yeast supplementation on milk performance, vitamin D content in milk, and blood metabolite profiles. Six crossbred Holstein Friesian cows were randomly allocated to treatment by using a 3 x 3 Double Latin square design, including a control group (T1), 5 g live yeast supplementation (T2), and 5 g vitamin D enriched yeast supplementation (160,000 IU/head/day; T3). Milk and blood samples were collected on days 28 of each trail period, for analyzing milk composition, vitamin D content in milk, and blood metabolite profiles. The result showed that the vitamin D enriched yeast supplementation group had 25-hydroxyvitamin D2 concentration in blood significantly higher than other comparable groups (64.27 compared to 47.39 and 49.31 ng/ml, respectively; P < 0.01). There were no significant differences between treatments for milk yield or ECM yield and milk composition but the vitamin D enriched yeast supplementation group had significantly higher vitamin D content in milk than the T1 and T2 groups (690.83 compared to 562.83 and 529.48 ng/1000mL, respectively; P < 0.01). As a result, supplementing vitamin D enriched yeast with dairy cow diets cloud improve vitamin D content in milk.